A novel peptide encoded by circSRCAP confers resistance to enzalutamide by inhibiting the ubiquitin-dependent degradation of AR-V7 in castration-resistant prostate cancer - Xiannan Meng; Qingxuan Wu; Chengsong Cao; Wendong Yang; Sufang Chu; Hongjun Guo; Suhua Qi; Jin Bai (Journal of Translational Medicine)
Abstract Background The sustained activation of androgen receptor splice variant-7 (AR-V7) is a key factor in the resistance of castration-resistant prostate cancer (CRPC) to second-generation anti-androgens such as enzalutamide (ENZ). The AR/AR-V7 protein is regulated by the E3 ubiquitin ligase STUB1 and a complex involving HSP70, but the precise mechanism remains unclear. Methods High-throughput RNA sequencing was used to identify differentially expressed circular RNAs (circRNAs) in ENZ-resistant and control CRPC cells. The coding potential of circSRCAP was confirmed by polysome profiling and LC–MS. The function of circSRCAP was validated in vitro and in vivo using gain- and loss-of-function assays. Mechanistic insights were obtained through immunoprecipitation analyses. Results A novel ENZ-resistant circRNA, circSRCAP, was identified and shown to be upregulated in ENZ-resistant C4-2B (ENZR-C4-2B) cells, correlating with increased AR-V7 protein levels. circSRCAP is generated via splicing by eIF4A3, forming a loop structure and is exported from the nucleus by the RNA helicase DDX39A. Mechanistically, circSRCAP encodes a 75-amino acid peptide (circSRCAP-75aa) that inhibits the ubiquitination of AR/AR-V7’s co-chaperone protein HSP70 by disrupting the interaction with the E3 ligase STUB1. This process results in the upregulation of AR-V7 expression and promotes ENZ resistance in CRPC cells. Xenograft tumor models further confirmed the role of circSRCAP in CRPC progression and its potential as a therapeutic target for ENZ-resistant CRPC. Conclusions circSRCAP provides an epigenetic mechanism influencing AR-V7 stability and offers a promising therapeutic target for treating ENZ-resistant CRPC.